Analysis of the Implementation of Training at the Department of Industry, Trade, Cooperatives and Small and Medium Enterprises - Dian Mutia; Fetri Yeni; Abna Hidayati; Rayendra Rayendra; Noviachri Imroatul Sadiyah (Universitas Negeri Semarang, 2025)
Background - Challenges in an era of continuous progress and competitive markets require groups, communities, organizations, and countries to demonstrate resilience and competitiveness. Knowledge is a vital asset that humans possess, and efforts to develop human resources are essential to support capacity building and promote competitive excellence. Research Urgency - SMEs frequently encounter challenges in managing their businesses, particularly due to their limited capacity to develop the products they produce. The UPT IPOK Disperindagkop and SMEs of Riau Province often conduct training for MSMEs to encourage improvements in the quality of human resources in Riau Province. However, there are still shortcomings in the implementation and evaluation of training activities held by the UPT IPOK. Research Objectives - This research aims to describe the planning, implementation, and evaluation of training at the Technical Implementation Unit of the Riau Province Industry, Trade, Cooperatives, and Small and Medium Enterprises Agency. Research Method - The research method is qualitative analysis. It consists of four stages. The first stage is data collection through in-depth interviews with 10 informants, comprised of the head of the IPOK Technical Implementation Unit, IPOK Technical Implementation Unit staff, IPOK Technical Implementation Unit SME extension workers, training instructors, and training participants. The second stage is data reduction, which is summarizing the results of the interviews conducted in accordance with the research needs. The fourth stage is data presentation, which involves compiling the collected data into a report and then conducting a qualitative analysis. Before proceeding to the fifth stage, validation is carried out again with the head of the IPOK Technical Implementation Unit, after which the fifth stage of concluding is carried out. Research Findings - The incubator training organizer contained an activity plan consisting of a legal basis, background, objectives, inputs, outputs, benefits, training location, participants, and activity schedule. The training ran smoothly thanks to the comprehensive facilities and infrastructure provided by the UPT IPOK. The evaluation showed that the instructors sought to improve the quality of the training based on the input provided by the participants. The evaluation was conducted in the form of a questionnaire that was filled out by the training participants. Research Conclusion - The training activity, which was attended by 10 participants, had a positive impact because it went through careful planning, adequate implementation, and sufficient evaluation, thereby creating jobs, increasing community income, and adding value to local raw materials to create superior products. Of course, this requires separate training on processing cassava. However, there are still obstacles related to marketing and capital. Research Novelty/Contribution - This study explains that in training activities, it is very important to have the continuity of advanced training needed by training participants. This is because when training is not completed to the point of producing SME independence, the benefits and objectives outlined in the training plan are not realized.